Evaluation of whiplash injuries by technetium 99m isotope scanning. Issue 3 (September 1993) - Barton, D; Allen, M; Finlay, D; Belton, I
Abstract : Despite the frequency with which whiplash injuries present to accident and emergency (A&E) departments, there lacks an objective investigation to define the severity of the initial injury or the morbidity that may ensue. Following reports on the effectiveness of isotope bone scanning for soft tissue and ligament injuries a study was undertaken of isotope scanning of whiplash injuries. The objectives of the study were to isolate the anatomic site of the injury and to quantify the severity of the injury with relation to the concentration of isotope uptake and subsequent morbidity.